The Adaptation of the Indonesian Version of the Maastricht Vital Exhaustion Questionnaire (MQ) Among Coronary Heart Disease (CHD) Patients: A Rasch Analysis: The Adaptation of the Indonesian Version of the Maastricht Vital Exhaustion Questionnaire (MQ) Among Coronary Heart Disease (CHD) Patients: A Rasch Analysis - Nuraeni, Aan; Widianti, Efri; Aziza, Aurelia Karla (Jurnal Surya Medika (JSM), 2024)
Background – The Indonesian version of the Maastricht Vital Exhaustion Questionnaire (MQ) is an instrument for assessing vital exhaustion in CHD patients. However, the psychometric results of this instrument have yet to be identified in the population of CHD patients in Indonesia. This study aims to evaluate the psychometric properties of the Indonesian version of the MQ instrument using Rasch analysis. Methods – The population of this study was all CHD patients undergoing outpatient treatment at a hospital in West Java. There were 97 respondents using convenience sampling. The instrument used is the Indonesian version of MQ. The reliability and validity of the instrument were analyzed using Rasch analysis and the Winsteps application by considering the Cronbach's Alpha value, Mean square fit statistic (MNSQ), Standardized fit statistics (ZSTD), separation of strata (Separation), and unidimensionality. Findings – α-Cronbach 0.78 with item reliability 0.95 indicates very good reliability; person and item strata separation >2.4 and >5.9, indicating the instrument can identify respondent groups well; MNSQ item infit-outfit 1-0.94 is close to ideal (1) as is ZSTD infit-outfit 0.11 – 0.03 (close to 0); Unidimensionality measurements show a total raw variance of 32.4% with unexplained eigenvalues all <10% indicating good validity. Conclusions - The internal consistency of the instrument is reliable. The data fits the model because the items can measure, have logical predictions, and functionally show unidimensionality. Based on the results, the Indonesian version of the MQ was proven valid and reliable for identifying vital exhaustion in CHD patients in Indonesia.